Benomyl, a benzimidazole fungicide, induces oxidative stress and apoptosis in neural cells. (2020) - Kara, Mehtap; Oztas, Ezgi; Ramazanoğulları, Rabia; Kouretas, Demetrios; Nepka, Charitini; Tsatsakis, Aristides M.; Veskoukis, Aristidis S.
Graphical abstract: Highlights: Benomyl exerts its toxic role by inhibiting microtubule formation in the nervous system. Benomyl induces oxidative stress, apoptosis and necrosis in neural cells. Benomyl is harmful even in low concentrations. The mechanism of action is redox-related. Abstract: Fungicides are used in the agricultural sector against the harmful action of fungi, however they are potential toxic agents for the environment and the living organisms. Benomyl is a widely encountered benzimidazole fungicide that exerts its toxicity via inhibiting microtubule formation in the nervous system and the male reproductive and endocrine systems, whilst it is a known teratogen. Since toxic effects of benomyl and its molecular mechanisms are not fully understood, we aimed to detect its neurotoxic potential via evaluating cytotoxicity, oxidative stress and apoptosis in SH-SY5Y cell line. The cells were incubated with benomyl in a concentration range between 1 and 6 μM for 24 h. Our results indicated a concentration-dependent enhancement of reactive oxygen species measured through flow cytometry and DNA damage evaluated via the comet assay. Additionally, it induced apoptosis in all tested concentrations. According to the findings of the present study, benomyl is a xenobiotic, which it appears to exert its toxic action via a redox-related mechanism that, finally, induces cell apoptosis and death. We believe that this study will offer further insight in the toxicity mechanism of benomyl, although further studies are recommended in order to elucidate these mechanisms in the molecular level.